The Politics of Service Delivery in Pakistan: Political Parties and the Incentives for Patronage, 1988-1999 - Hasnain, Zahid (2012)
This paper examines the impact of the political party structure on the incentives for politicians to focus on patronage versus service delivery improvements in Pakistan. By analysing inter-provincial variations in the quality of service delivery in Pakistan, the paper argues that the more fragmented, factionalised, and polarised the party systems, the greater are the incentives for patronage, weakening service delivery improvements. Fragmentation and factionalism both exacerbate the information problems that voters have in assigning credit (blame) for service delivery improvements (deterioration), thereby creating the incentives for politicians to focus on targeted benefits. Polarisation, particularly ethnic polarisation, reduces the ability of groups to agree on the provision of public goods, again causing politicians to favour the delivery of targeted benefits.